Proline-induced hinges in transmembrane helices: possible roles in ion channel gating. - Tieleman, D; Shrivastava, I; Ulmschneider, MR; Sansom, MS (2001)
A number of ion channels contain transmembrane (TM) alpha-helices that contain proline-induced molecular hinges. These TM helices include the channel-forming peptide alamethicin (Alm), the S6 helix from voltage-gated potassium (Kv) channels, and the D5 helix from voltage-gated chloride (CLC) channels. For both Alm and KvS6, experimental data implicate hinge-bending motions of the helix in an aspect of channel gating. We have compared the hinge-bending motions of these TM helices in bilayer-like environments by multi-nanosecond MD simulations in an attempt to describe motions of these helices that may underlie possible modes of channel gating. Alm is an alpha-helical channel-forming peptide, which contains a central kink associated with a Gly-x-x-Pro motif in its sequence. Simulations of Alm in a TM orientation for 10 ns in an octane slab indicate that the Gly-x-x-Pro motif acts as a molecular hinge. The S6 helix from Shaker Kv channels contains a Pro-Val-Pro motif. Modeling studies and recent experimental data suggest that the KvS6 helix may be kinked in the vicinity of this motif. Simulations (10 ns) of an isolated KvS6 helix in an octane slab and in a POPC bilayer reveal hinge-bending motions. A pattern-matching approach was used to search for possible hinge-bending motifs in the TM helices of other ion channel proteins. This uncovered a conserved Gly-x-Pro motif in TM helix D5 of CLC channels. MD simulations of a model of hCLC1-D5 spanning an octane slab suggest that this channel also contains a TM helix that undergoes hinge-bending motion. In conclusion, our simulations suggest a model in which hinge-bending motions of TM helices may play a functional role in the gating mechanisms of several different families of ion channels.